Menace of Kidnapping and Challenges of Post Abduction Living - Yakubu, S. Muhammad (Kashere Journal of Education, 2022)
Kidnapping refers to crime of seizing, confining, abducting, or carrying away a person by force or fraud, often to subject him or her to involuntary servitude in an attempt to demand for a ransom. The paper looked at the concept of kidnapping, prevalence of kidnapping, a concise history of kidnapping in Nigeria, strength of kidnapping in Nigeria, Menace of Kidnapping and Challenges of Post Abduction Living and recovery and future. Some of the recommendations highlighted include; released hostage should receive resources and information about how to see counseling, youths should be provided with enabling environment that would make them relevant in the scheme of things in Nigeria.